PENINGKATKAN KETERAMPILAN GURU BIMBINGAN KONSELING DALAM PEMEROLEHAN KESIAPAN PSIKOLOGIS SISWA MENGHADAPI BENCANA ALAM - Yulia Ayriza (Jurnal Cakrawala Pendidikan, 2011)
Abstract: Improving Guidance and Counseling Teachers’ Skills in the Acquisition of Students’ Psychological Preparedness for Natural Disasters. This study aims to investigate whether there is an improvement of school councelors’ skills in carrying out personal-social guidance and counseling after joining a module implementation training on the improvement of students’ psychological preparedness for natural disasters. This was a quasi-experimental study involving 29 high school counselors in the Province of Yogyakarta Special Territory. The sample was selected using the area quota random sampling technique. The data collecting instruments consisted of a test, scale, and observation. The data were analyzed using the t-test with the SPSS program. The result showed that there was a significant increase in school counselors’ skills, before and after the module implementation training, in carrying out personal-social counseling services with the aim of improving students’ psychological preparedness for natural disasters. Keywords: school counselors’ skills, psychological preparedness for natural disasters